Strategic Growth with Recursive Preferences: Decreasing Marginal Impatience - Alcalá, Luis Adrián (2018)
This paper studies a two-agent strategic model of capital accumulation with heterogeneity in preferences and income shares. Preferences are represented by recursive utility functions that satisfy decreasing marginal impatience. The stationary equilibria of this dynamic game are analyzed under two alternative information structures: one in which agents precommit to future actions, and another one where they use Markovian strategies. In both cases, we develop sufficient conditions to show the existence of these equilibria and characterize their stability properties. Under certain regularity conditions, a precommitment equilibrium shows monotone convergence of aggregate variables, but Markovian equilibria may exhibit nonmonotonic paths, even in the long-run.